Peran Kompetensi Kepala Sekolah, Efektivitas Supervisi Pengawas Terhadap Motivasi Berpretasi, Disiplin Kerja Dan Produktivitas Sekolah Di SMA N 1 Yogyakarta - Keson, Bajur, Prof. Sutama, M.Pd (2016)
The objectives of this reseach are to know the biggest direct influence and indirect independent variable toward dependent variable. The reseach design uses non-experimental quantitative approach, to examine the facts that have occurred and experienced by subjects of research (ex post facto). The data analysis using descriptive analysis and path analysis to determine the direct and indirect influence of the independent variable. The results showed achievement motivation of teachers influenced by the effectiveness of supervision supervisior (SE 6.89%) and the competence of the principals (SE 0.68%). Discipline teacher work jointly influenced by the effectiveness of supervision supervisior (SE 6.65%), the second order of achievement motivation (SE 4.4%) and the competence of the principals (SE 0.04%). Productivity schools are directly or indirectly influenced the competence of the principals (0.40%), work discipline teachers (0.68%), achievement motivation (4.4%) and the highest by the effectiveness og the regulatory supervision (6.55%). Through path analysis it turned out, the path coefficient value is greater than the direct effect of the indirect effect, so effect is actually a direct influence.